Cultural influences upon advance care planning in a family-centric society. Issue 6 (8th February 2017) - Tay, Keson; Yu Lee, Rachel Jia; Sim, Shin Wei; Menon, Sumytra; Kanesvaran, Ravindran; Radha Krishna, Lalit Kumar
ABSTRACT: Objective: Advanced care plans (ACPs) are designed to convey the wishes of patients with regards to their care in the event of incapacity. There are a number of prerequisites for creation of an effective ACP. First, the patient must be aware of their condition, their prognosis, the likely trajectory of the illness, and the potential treatment options available to them. Second, patient input into ACP must be free of any coercive factors. Third, the patient must be able to remain involved in adapting their ACP as their condition evolves. Continued use of familial determination and collusion within the local healthcare system, however, has raised concerns that the basic requirements for effective ACP cannot be met. Method: To assess the credibility of these concerns, we employed a video vignette approach depicting a family of three adult children discussing whether or not to reveal a cancer diagnosis to their mother. Semistructured interviews with 72 oncology patients and 60 of their caregivers were conducted afterwards to explore the views of the participants on the different positions taken by the children. Results: Collusion, family-centric decision making, adulteration of information provided to patients, and circumnavigation of patient involvement appear to be context-dependent. Patients and families alike believe that patients should be told of their conditions. However, the incidence of collusion and familial determination increases with determinations of a poor prognosis, a poor anticipated response to chemotherapy, and a poor premorbid health status. Financial considerations with respect to care determinations remain secondary considerations. Significance of results: Our data suggest that ACPs can be effectively constructed in family-centric societies so long as healthcare professionals continue to update and educate families on the patient's situation. Collusion and familial intervention in the decision-making process are part of efforts to protect the patient from distress and are neither solely dependent on cultural nor an "all-or-nothing" phenomenon. The response of families are context-dependent and patient-specific, weighing the patient's right to know and prepare and the potential distress it is likely to cause. In most cases, the news is broken gently over time to allow the patient to digest the information and for the family to assess how well they cope with the news. Furthermore, the actions of families are dependent upon their understanding of the situation, highlighting the need for continued engagement with healthcare professionals.